LEGAL ANALYSIS OF THE SALE AND PURCHASE OF PHOTO IDOL - Anggelita Hanryanti; Emy Rosna Wati (PT. Antis International Publisher, 2025)
Objective: This research discusses what events occur in the context of buying and selling photo idols and the purpose of this research is to examine how the government tackles various cases in the realm of buying and selling photo idols. Method: This research method uses normative juridical method. The research legal materials include primary and secondary. Result: The results state that the crimes that often occur are scammers and defaults. Perpetrators who intentionally commit scammer crimes can be sanctioned in accordance with Article 45 paragraph (1) of the ITE Law. Meanwhile, sellers who commit default can be sanctioned in accordance with article 62 paragraph (1) of the Consumer Protection Law. Novelty: To overcome these crimes, the government has made various efforts such as creating a complaint website, a website to check account numbers or telephone numbers, but the government still has several obstacles.